PENGARUH TRANSPARASI RAPBS, SUPERVISI KEPALA SEKOLAH DAN PENGALAMAN MENGAJAR GURU TERHADAP MUTU PEMBELAJARAN GURU ADAPTIF SMK NEGERI KELOMPOK TEKNOLOGI DAN REKAYASA SE-KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine the effect of RAPBS transparency, principal supervision and teachers’s teaching experience jointly or individually on teaching learning qualityThis research was conducted at SMK Group Technology and Engineering in the District Kebumen. This research is quantitative used survey method. The population of the study was 157 teachers in State Technology and Engineering SMK in Kebumen. Samples were 120 teachers. The sampling technique used is proportional random sampling. Data collection techniques using questionnaires and data analysis techniques using multiple regression analysis and partial correlation.The results indicated a significant positive influence RAPBS transparency, principal supervision and teachers’s teaching experience together and individually on teaching learning quality. It can be explained that if the RAPBS transparency, principal supervision and teachers’s teaching experience have increased the teaching learning quality will also increase. There was a significant positive influence RAPBS transparency on teaching learning quality. It can be explained that if the RAPBS transparency increases, the teaching learning quality will increase. There was a significant positive influence principal supervision on teaching learning quality. It can be explained that if the principal supervision has increased, then the teaching learning quality will increase. There is a very significant positive effect of teachers’s teaching experience on teaching learning quality. It can be explained that if the teaching experience of teachers is increasing the teaching learning quality will be increased.